teknika DATA MINING TO PREDICTE STUDENT ACHIEVEMENT BASED ON SOCIO-ECONOMIC, MOTIVATION, DISCIPLINE AND PAST ACHIEVEMENT AT VOCATIONAL SCHOOL 1 PENAWARTAMA TULBABAG USING THE C4.5 ALGORITHM: DATA MINING UNTUK MEMPREDIKSI PRESTASI PESERTA DIDIK BERDASARKAN SOSIAL EKONOMI, MOTIVASI, KEDISIPLINAN DAN PRESTASI MASA LALU DI SMKN 1 PENAWARTAMA TULANG BAWANG MENGGUNAKAN ALGORITMA C4.5 - Suroto, Suroto; Purnomo, Hendri; Estian Pambudi, Randi (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
SMK Negeri 1 Penawartama Tulang Bawang is a school whose students come from various villages in the district. Most of the students come from families with limited economic conditions and low levels of education. These factors often affect the students' learning motivation. The aim of this research is to predict students' academic performance based on parents' socioeconomic status, motivation level, discipline level, and previous academic achievements using data mining methods with the C4.5 algorithm. This research employs a quantitative approach involving 606 tenth-grade students at SMK Negeri 1 Penawartama Tulang Bawang. Data collection methods used include documentation and questionnaires. The research results show that the prediction analysis using decision trees has an accuracy rate of 98.02%, precision of 94.44%, and recall of 77.27%. Â  Keywords: data mining, C4.5 algorithm, accuracy, precision, and recall